Teaching the economics of automation - Jahangir, Junaid (My University, 2024)
The purpose in this paper is to create a teaching module on the economics of automation. Avoiding technicalities but focusing on critical thinking, key ideas in the economics of automation are highlighted,and class discussion material is provided based on popular books published in the 2020s. Differing perspectives from these books allow for rich class discussions on topics including the risks of automation, the power of Big Tech, and policy responses for the digital economy. For ECON 101 students, Disney animation clips are provided as hooks to engage in analogy-based understanding of issues in automation. Likewise, other video clips are used to discuss the risks and dangers of automation related to jobs, scams, democracy, and political polarization. Overall, this teaching module highlights key ideas in the economics of automation, incorporates ideas from recently published books, and complements the lecture with videos to retain student interest
Keywords: economics of automation; artificial intelligence; risks of automation; ChatGPT